2016
DOI: 10.3390/coatings6010003
|View full text |Cite
|
Sign up to set email alerts
|

On Modulating Interfacial Structure towards Improved Anti-Icing Performance

Abstract: Abstract:The design of anti-icing surfaces presents an interface with high causal density that has been challenging to quantify in terms of individual contributions of various interactions and environmental factors. In this commentary, we highlight the role of interfacial water structure as uniquely expressing the physico-chemical aspects of ice accretion. Recent work on the topic that focuses on control of interfacial structure is discussed along with results by our research group on wettability of chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 174 publications
0
18
0
Order By: Relevance
“…The key to coating designs for reduced ice adhesion is to select materials with a low bonding strength to H 2 O. The effects of hydrogen bonds on the interface bonding have been studied by many researchers [32,37,38]. Using a range of mixtures of zero hydrogen bonding with a hydrophobic surface as sembled monolayer (SAM) of 1 dodecanethiol and a surface with a hydrophilic nature like a SAM of 11 hydroxylundecane 1 thiol, ex perimentally determined ice adhesion values showed that hydrogen bonding was the greatest contributing factor to ice adhesion [38].…”
Section: General Coating Classification and Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key to coating designs for reduced ice adhesion is to select materials with a low bonding strength to H 2 O. The effects of hydrogen bonds on the interface bonding have been studied by many researchers [32,37,38]. Using a range of mixtures of zero hydrogen bonding with a hydrophobic surface as sembled monolayer (SAM) of 1 dodecanethiol and a surface with a hydrophilic nature like a SAM of 11 hydroxylundecane 1 thiol, ex perimentally determined ice adhesion values showed that hydrogen bonding was the greatest contributing factor to ice adhesion [38].…”
Section: General Coating Classification and Requirementsmentioning
confidence: 99%
“…In terms of ice adhesion strength, there exists a large variation in the published work for an individual substrate. This is in part due to the wide spectra of icing test conditions, ice thickness, the use of different adhesion test methods (lap shear, centrifuge, 0°cone test, bend test, knife edge test, impact [15,37]) and experimental variables. A review of the various testing methods and the measurements resulting from each test can be found in Ref.…”
Section: General Coating Classification and Requirementsmentioning
confidence: 99%
“…The problems related to ice adhesion on structures is a global annoyance which has caused and is still causing threat to industry and public safety in many parts of the world, including North American (USA, Canada), Asian (Japan, China) European and Scandinavian countries, as reflected by the research contributions in this Special Issue by authors from these countries who constantly strive to minimize its impacts [1][2][3][4][5][6][7][8][9][10]. World renowned experts have been addressing the ice adhesion issues with their advanced research and development and in the finding of advanced technologies to evaluate the adhesion phenomena, both theoretically and experimentally.…”
mentioning
confidence: 99%
“…The ten contributions constituting this Special Issue are composed of the latest developments and the state of the art regarding ice adhesion, which are well elaborated for a wide range of readers, including research scientists, students and industrials, as well as the curious audience. These ten contributions originate from countries worldwide, namely, Canada (Quebec), Italy, Spain, China, Norway, Germany, Bulgaria and USA [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation